PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BANK CENTRAL ASIA TBK KCP PASAR MINGGU JAKARTA SELATAN - Nuraeni, Febi; Prabowo, Budhi (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of work discipline and work environment on employee performance at PT Bank Central Asia Tbk KCP Pasar Minggu, South Jakarta. The method used is quantitative analysis. The sampling technique used saturated sampling and a sample of 63 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that work discipline and the work environment have a positive and significant effect on employee performance with the regression equation Y = 7.280 + 0.336X1 + 0.498X2. The coefficient of determination has a simultaneous effect of 72.9%. Partially testing the hypothesis obtained a work discipline figure (X1) of tcount > ttable (11.544 > 1.670). So Ho is rejected and Ha1 is accepted. This means that there is a xiiositivee and significant influence between the work discipline variable (X1) on employee performance (Y). Work environment (X2) is t count > t table (11.544 > 1.670). So Ho is rejected and Ha is accepted. This means that there is a positive and significant influence between work environment variables (X2) on employee performance (Y). Hypothesis testing obtained F count > F table or (80.564 > 3.15). Thus, Ho is rejected and H3 is accepted, meaning that work discipline (X1) and work environment (X2) together have a positive effect on employee performance (Y).